Prevalensi Problem Depresi pada Pasien Diabetes Mellitus di Puskesmas - Puspita, Salma Fajar; Saepudin (Universitas Islam Indonesia, 2024)
Background: Depression is a common psychological disorder in diabetic patients that potentially causes non-adherence and complications. However, information regarding the prevalence and risk factor of depression in diabetic patients in Indonesia remains inconsistent.Objective: This study is aimed to determine the prevalence of depression and its associated factors among patients with type II diabetes mellitus (T2DM) in primary public health centers.Method: This cross-sectional study involved adult patients with T2DM in primary health centers in Sleman, Indonesia. Subjects were recruited using the purposive sampling method, and depression was assessed using the PHQ-9 questionnaire. The association between subject characteristics and depression was determined using the chi-square of Fisher’s exact test. Results: Among 268 subjects, most of them were women, aged <60 years old, had at least 1 comorbidity, and were taking a combination of oral antidiabetics. More than half of subjects had T2DM for <5 years. The prevalence of depression among T2DM was 36.6%. Being aged ≥60 years old, having a low education level, being a provider of family, and having T2DM for 5-10 years (p<0.05) were significantly associated with depression.Conclusion: T2DM patients aged ≥60 years old, who have a low education level, are providers of family, and have had T2DM for 5-10 years are more vulnerable to depression, thus needing more attention from healthcare providers to achieve diabetes goal therapy.